What mean impacts miss: distributional effects of welfare reform experiments - Hilary W. Hoynes; Marianne P. Bitler; Jonah B. Gelbach (University of California, Department of Economics, 2005)
Labor supply theory predicts systematic heterogeneity in the impact of recent welfare reforms on earnings, transfers, and income. Yet most welfare reform research focuses on mean impacts. We investigate the importance of heterogeneity using random-assignment data from Connecticut's Jobs First waiver, which features key elements of post-1996 welfare programs. Estimated quantile treatment effects exhibit the substantial heterogeneity predicted by labor supply theory. Thus mean impacts miss a great deal. Looking separately at samples of dropouts and other women does not improve the performance of mean impacts. We conclude that welfare reform's effects are likely both more varied and more extensive than has been recognized.
Keywords: 330; Sozialhilfe; Reform; Arbeitsangebot; Lohn; Sozialtransfer; Haushaltseinkommen; Soziale Wohlfahrtsfunktion; USA; Verteilungswirkung